116 Early life body size and risk of systemic lupus erythematosus. (April 2019) - Jacobsen, Soren; Thomas, Peter Engel; Aarestrup, Julie; Sørensen, Kathrine Kold; Jensen, Britt Wang; Baker, Jennifer Lyn
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. Adult obesity may increase risks of SLE. SLE autoantibodies have been detected in patients many years prior to a SLE diagnosis, suggesting that etiological factors may influence SLE risks early in life. Child or adult height as a risk factors for SLE has not been investigated. However, there are suggestions of a genetic link between SLE and tall adult height. The evidence of an association between birth weight and SLE risks is inconsistent. We therefore investigated whether birth weight, childhood body mass index (BMI [kg/m 2 ]), and height are associated with later risks of SLE. Methods: We used the Copenhagen School Health Records Register which contains annual weight and height measurements at ages 7 to 13 years on 4 06 308 children born from 1930–1996 who attended schools in Copenhagen. Information on birth weight was obtained from 1936 onwards. SLE diagnosis was obtained through linkage to the Danish National Patient Register using unique personal identification numbers. Cox hazard regressions were performed to estimate hazard ratios (HR) and 95% confidence intervals (CI). Results: 3 46 545 children (1 75 494 boys) were included. During 40 years of follow-up there were 435 cases of SLE (69 men). As there were no significant interactions with sex, analyses are presented for sex combined. For birth weight there was no significant association with SLE. For childhood BMI there was a positive and significant, or borderline significant, association with SLE at all childhood ages. At age 13 years the HR was 1.13 (95% CI: 1.02–1.26) per BMI z-score and HRs were similar across all ages. For childhood height there were significant and positive associations with SLE at all childhood ages. At age 13 years the HR was 1.12 (95% CI: 1.01–1.23) per height z-score and HRs were similar across all ages. Conclusions: These findings of positive associations between childhood BMI and height and SLE risk suggest that early life factors may be important in the etiology of SLE. Funding Source(s): University of Copenhagen Fund for Medical Students and University of Copenhagen, Faculty of Health and Medical Sciences Fund, Gigtforeningen.